-2(-2b-7)=-2(1+4b)+4b

Simple and best practice solution for -2(-2b-7)=-2(1+4b)+4b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-2b-7)=-2(1+4b)+4b equation:


Simplifying
-2(-2b + -7) = -2(1 + 4b) + 4b

Reorder the terms:
-2(-7 + -2b) = -2(1 + 4b) + 4b
(-7 * -2 + -2b * -2) = -2(1 + 4b) + 4b
(14 + 4b) = -2(1 + 4b) + 4b
14 + 4b = (1 * -2 + 4b * -2) + 4b
14 + 4b = (-2 + -8b) + 4b

Combine like terms: -8b + 4b = -4b
14 + 4b = -2 + -4b

Solving
14 + 4b = -2 + -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
14 + 4b + 4b = -2 + -4b + 4b

Combine like terms: 4b + 4b = 8b
14 + 8b = -2 + -4b + 4b

Combine like terms: -4b + 4b = 0
14 + 8b = -2 + 0
14 + 8b = -2

Add '-14' to each side of the equation.
14 + -14 + 8b = -2 + -14

Combine like terms: 14 + -14 = 0
0 + 8b = -2 + -14
8b = -2 + -14

Combine like terms: -2 + -14 = -16
8b = -16

Divide each side by '8'.
b = -2

Simplifying
b = -2

See similar equations:

| 1.79g-11=0.57 | | (-8/9)-5)3 | | 4x+9y=-5 | | -6x+10=-38+2x | | 5y+9=7(y-3) | | 1.79-11=0.57 | | 30=2h+6I | | 25y^10-t^8=0 | | (3/2)x-(5/4)y=15 | | 3i(5+2i)-2(5-4i)=0 | | -7+11g=9-11g | | 70+2x=68+1.5x | | X+2=6x+22 | | X+12=140 | | -(x+8)(x-5)=0 | | -(x^5-20x^3+64x)=0 | | 12x-47+5=18 | | (8/9)-5)3 | | -2(-3x-8)=58 | | xy-5xy^2= | | 21=-18 | | h3/h-6 | | 4x+14-6x+22=4 | | 3y^2-20y+15=0 | | -x+9=-5x+57 | | (-x+9i)(x-9i)=0 | | 5/(x-3)-6=12/(x-3) | | 7x+2=2x+1 | | 116=121-x | | 5-3/12 | | 3=-4(1)+b | | a^2+9=9 |

Equations solver categories